SALIVA AND SERUM LEVELS OF TNF-α AND IL- 6 IN A SAMPLE OF ROMANIAN ADULT SUBJECTS WITH TYPE 2 DIABETES MELLITUS AND PERIODONTAL DISEASE - Monea, Adriana; Gruber, Reinhard; Elod, Nagy; Bereşescu, Gabriela; Moldovan, Cosmin; Monea, Monica (European Scientific Journal, ESJ, 2014)
Introduction: Patients with diabetes mellitus can exert a stronger inflammatory response compared to systemically healthy individuals; however, if this accounts true patients with periodontal disease remains unclear. We therefore determined salivary and serum TNF-α and IL-6 levels in periodontal patients, with or without type 2 diabetes mellitus (T2D) Material and methods: Twenty type 2 diabetes mellitus subjects with periodontal disease, 21 systemically healthy subjects with periodontal disease and 21 healthy controls were enrolled in the study. Periodontal indices, HbA1c levels as well as saliva and serum TNF-α and IL-6 were reported. Results: TNF-α and IL-6 levels in the saliva were higher in type 2 diabetes mellitus subjects with periodontal disease compared to systemically healthy subjects with periodontal disease. Healthy controls showed lower TNF-α and IL-6 levels in the saliva than subjects with periodontal disease. The respective serum analysis, however, revealed only a minor impact of the type 2 diabetes mellitus and periodontal disease on TNF-α and IL-6 levels. Conclusions: The data support the current hypothesis that the inflammation linked to periodontal disease is more severe in type 2 diabetic patients compared to the systemically healthy individuals.